The importance of presidential leadership for Brazilian foreign policy. (4th May 2017) - Burges, Sean W.; Chagas Bastos, Fabrício H.
ABSTRACT: The conventional wisdom in Brazil is that foreign policy is a policy of state and, as such, not part of the daily political debate. The result is an understanding that foreign policy is largely driven by the foreign ministry, with the president generally only taking a role when needed to advance a particular initiative through presidential diplomacy. We challenge these assumptions, arguing that the engagement and authority of the president are the essential factors in bringing about not only substantive strategic change in Brazilian foreign policy, but also alterations in the policy process that have democratized foreign policy and moved it from a policy of state to another area of public policy. To do this, we draw on and deepen Sergio Danese's theory of presidential diplomacy and map out major strategic changes in post-authoritarian Brazil's foreign policy. We find that the major changes that have taken place were initiated by the truncated Fernando Collor presidency and then deepened and amplified by the highly internationally engaged presidencies of Fernando Henrique Cardoso and Lula. By contrast, the presidencies of Itamar Franco and Dilma Rousseff emerge as instances of inertial continuity lacking in dynamism and innovation.